THE RELATIONSHIP BETWEEN CADETS' ACADEMIC COMPETENCE AND PERFORMANCE DURING FLIGHT OPERATIONS OFFICER ON-THE-JOB TRAINING AT PT CITILINK INDONESIA - Rico Darmawan; Khoirunnisa Larasati; Herdi Santoso; Dimas Hari Cahyo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Aviation vocational education requires alignment between theoretical knowledge and the ability to perform operational tasks effectively. This study aimed to analyze the level of cadets' academic competence, the level of practical performance, and the relationship between the two during the On-the-Job Training (OJT) program for Flight Operations Officers (FOOs) at PT Citilink Indonesia. The study employed a quantitative descriptive correlational design. The primary analysis involved all 126 cadets of the Aircraft Operations Study Program at the Indonesian Aviation Academy Banyuwangi who had complete academic records and OJT performance evaluations. Academic competence was measured using the average scores of 17 FOO-related subjects, while OJT performance was measured based on supervisors' evaluations covering FLOPS, RAMP, Flight Following, Crew Tracking, and Work Habit. The data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and Spearman's rank correlation. As supporting data, a perception questionnaire was administered to 65 cadets, with the sample size determined using the Slovin formula. The results showed that the mean academic competence score was 84.67, which falls into the Very Good category, while the mean OJT performance score was 87.75, categorized as Satisfactory. Both variables were not normally distributed. Spearman's rank correlation analysis yielded a correlation coefficient of ρ = –0.196 with p = 0.028, indicating a statistically significant but very weak negative relationship. The questionnaire findings revealed that academic competence provided a fundamental basis for performing OJT tasks; However, cadets still perceive differences between campus-based learning and airline operational practices, particularly regarding operational procedures, company systems, and operational applications. The study concludes that academic competence is significantly associated with OJT practical performance, although the strength of the relationship is very weak and therefore does not fully explain OJT performance. The findings suggest that educational institutions should strengthen operational simulations, introduce airline operational systems, and further align academic learning with industry requirements